Conciliação de medicamentos direcionada a pacientes internados em hospital psiquiátrico: descrição e análise - Silva, Rebeca Sampaio Barros Monte e (2021)
The polypharmacy is a reality in hospitalized patients, especially in psychiatry, where an association of medications is common for therapeutic success. In addition, at the time of hospital admission, changes in the medications already used by the patient are common and discrepancies may occur. The unintentional discrepancies or medication errors can compromise patient safety. The pharmaceutical medication reconciliation service has great potential to identify and resolve these discrepancies. The objective of this study was to perform the medication reconciliation service in psychiatric patients. A cross-sectional, prospective, research-action research was carried out in a psychiatric hospital in the state of Ceará. The study was carried out from January 2020 to March 2020 with patients admitted to the hospital during this period. Research was developed in four stages. In the first stage, the project was initially presented to other health professionals. In the second, using the medication reconciliation form, all data related to the patient's pharmacotherapy were collected from medical records. In the third, discrepancies were identified and classified and in the final step, pharmaceutical interventions were carried out with the prescribers. The Statistical Package for the Social Sciences (SPSS) program was used for data analysis. The research was only carried out after approval by the Research Ethics Committee of the Federal University of Ceará (UFC). The study was conducted with a sample of 363 patients and most of these patients were male (65%), single (78.5%), the predominant age group was 21 and 30 years (33,3%), had previous psychiatric hospitalizations (74.4%) and involuntary hospitalization (95%). The most prevalent hospitalization diagnoses were bipolar affective disorder (22.1%) and schizophrenia (21.88%). Patients used an average of 4.2 medications during hospitalization and the most prescribed classes were antipsychotic (38.1%) and anxiolytics (14.8%). In 151 patients, it was not possible to perform conciliation, mainly due to the abandonment of the previous treatment. Of the 212 reconciled patients, 197 had at least one discrepancy. A total of 599 discrepancies were identified and classified, in which corresponds to 554 intentional discrepancies and 45 unintentional discrepancies. The most frequent unintentional discrepancy was omission with more than 50%. Finally, 44 pharmaceutical functions were performed and about 93% were accepted by the prescriber.Therefore, a reconciliation of medications at the time of hospital admission for an effective strategy to identify discrepancies and coupled with pharmaceutical intervention to avoid medication errors, improving patient safety during psychiatric hospitalization.